Searching for mitochondrial targets of the ubiquitin ligase APC/CCdh1 - Tavares, Maria Barbedo Ramalho Figueiredo (2023)
The Anaphase promoting Complex/Cyclosome (APC/C) is an E3 ubiquitin ligase involved in cell cycle progression by targeting cell-cycle regulators for degradation. It is conserved from yeast to humans and relies on two adaptor proteins, Cdc20 and Cdh1, which identify its substrates due to the presence of recognition motifs. In humans, Cdh1 recognizes a broader set of substrates than Cdc20, including Drp1, a protein involved in mitochondrial fission. Unpublished studies from our group revealed that Atp2, an ATPsynthase subunit, is also increased in the absence of Cdh1 suggesting that APC/CCdh1 may play a broader role in mitochondrial function than expected. As such, the objectives of this work were to investigate the role of APC/CCdh1 in mitochondrial function using a proteomic approach, and identify the players involved. We used high-resolution mass spectrometry to obtain a global view of the impact of Cdh1 on the yeast mitochondrial proteome. With a coverage of ~97%, we found 12% of proteins have a significantly increased abundance in the absence of CDH1. These included subunits from all the respiratory complexes, enzymes from the Krebs cycle and regulators of mitochondria morphology (including Dnm1/Drp1). These protein classes are known to be essential for the adaptation of mitochondria to respiratory metabolism. We also found that 19% of the proteins were downregulated, being associated to non-respiratory processes. Interestingly, nearly all the cdh1Δ-altered proteins have the signature of 4 transcription factors (TFs), Rpn4, Pdr3, Yap1, and Gcn4, suggesting Cdh1 may be regulating mitochondrial proteins by targeting TFs. Supporting this hypothesis, the higher Atp2 levels and mitochondrial respiration in cdh1Δ strain decreased upon RPN4 and YAP1 deletion indicating these stress response TFs act downstream of Cdh1. In agreement, Yap1 is transcriptionally more active in the absence of Cdh1 and its absence decreases the slow growth of cdh1Δ cells. In addition, Yap1 protein levels are strongly decreased in the G1 phase of the cell cycle, in which APC/CCdh1 activity peaks, suggesting Cdh1 targets Yap1 for degradation. Overall, these results indicate a novel role for Cdh1 in the regulation of mitochondrial metabolic remodeling through Yap1 regulation. Regulation of Yap1 during cell cycle may allow coupling the known transient increase in mitochondrial respiration, important to meet cell cycle energetic demands, with the expression of antioxidant defenses, vital to mitigate the reactive oxygen species byproducts of respiration.